PENATALAKSANAAN FISIOTERAPI PADA KONDISI CEREBRAL PALSY HIPERTONUS SPASTIK ATHETOID DIPLEGI MENGGUNAKAN METODE NEURO DEVELOPMENT TREATMENT DAN BRAIN GYM DI YPAC SURAKARTA - Karina Eka Ratnasari; Nur Susanti (LPPM Universitas Pekalongan, 2016)
Cerebral Palsy (CP)is a collection of symptoms abnormalities motor development and posture caused by impaired brain development in the womb or future child - a child. Athetoid Cerebral palsy is a disorder that has the characteristics write uncontrolled movements and slowly. Causes Cerebral palsy can be divided into 3 parts: prenatal, natal and post natal. Physiotherapy problematic in the case of the presence of spasticity, muscle spasms, primitive reflexes, postural control, decrease functional activity, the sensory disorders. Physiotherapy goal to determine the effect of neurodevelopment stimulation treatment and Brain Gym in the decrease in spasticity, reduction in muscle spasm, control the primitive reflexes, increased postural control, increasing the functional activity, improve sensory abilities. The research design used in scientific papers arekasus.Kasus research study design scientific paper is taken in the Foundation Development of Disabled Children (YPAC) Surakarta.